Spring-back simulation of flat symmetrical laminates with angled plies manufactured through autoclave processing - Mohd Nasir, Mohd Narizee; Aminanda, Yulfian; Mezeix, Laurent; Seman, Mh Adam; Rivai, Ahmad; Ali, Karim M (IOP Publishing, 2016)
This paper presents a non-linear finite element analysis (FEA) method to predict the spring-back deformation for composite structures manufactured using autoclave processing. It is a progression from previous accompanying study on flat unidirectional samples and the aim is to observe spring-back warpage on laminates consisting of angled (±45o) plies compared to unidirectional (0o) laminate. Three samples for each of the symmetrical laminates with angled plies [45/0]S and [45/-45]S are manufactured and the warpage form is observed. FEA model that was utilized in the previous study, along with the physical mechanisms of spring-back such as the first ply stretching and tool-part interaction mechanisms, are maintained with only changes in material orientation for the part and the tool-part interface components. Upon comparison, the data shows that the spring-back form for symmetrical laminate becomes more complex to predict.